Influence of Dietary Cation-Anion Difference Based Diet on Nutrient Intake and Growth Performance of Crossbred Calves in Winter - Sambyal, Madhu suman; Kaur, Harhit; Phondaba, Bhupendera Tulsidas; Katoch, Shivani; Mor, preeti (Indian Journal of Animal Nutrition, 2018)
The present study was conducted on eighteen female crossbred calves for 120 days to examine the influence of varying dietary cation anion difference (DCAD) based diet on nutrient utilization and growth performance of crossbred calves in winter months. The calves were blocked into three equal groups on the basis of average body weight. The calves either received a basal diet (control) or +150 /+250 mEq/ Kg dry matter (DM) DCAD diets (W1, W2). The overall DMI was significantly more (P<0.05) in treatment groups. The growth rate was significantly more (P <0.05) in W2 group as compared to control. N intake, balance and urine pH increased significantly (P<0.05) with increasing level of DCAD. It was concluded that positive DCAD diet (+250 mEq/ Kg DM) increased nutrient intake, body weight gain in crossbred calves during winter months.